Model matematik ekstraksi sari buah dengan pengembangan unuaksial=Mathematical modelling of juice expressian under uniaxial compression - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRAK The juice expression under compression was applied within fruit processing frequently. The first objectives of this research was the modelling of uniaxial compression phenomena based on physic models as specimens. The second was applied simulation model for uniaxial compression within semi solid system of bengkuang pulp and coconut pulp as specimens. The semi empirical model was developed based on dimension analysis of plastic foam and carboxhymethyl cellulose (CMC) as specimens. With the variations of independent variabels in the dimensionless number function such as diameter and deformation of specimens, compression velocities, time for relaxation, initial liquid content, and viscosity of liquid. They influenced dependent variabels such as compression force, sum of liquid expression, and bulk density of specimens. The simulation model was composed on mass conservation, the fluid flow through bed, distribution of pressure, and relationship between pressure and porosity equations. The assumption linear relationship of compression pressure with bed porosity, and used the juice expression rate data, could be found parameter G and K of the model. The results of this research based on validity test models showed that semi empirical model had been compiled to give the valid prediction of dependent variabels, and also the application simulation model had been compiled to give the valid prediction juice expression rate along with compression pressure and period respectively.